Distribution of TRPV1 and TRPV2 in the human stellate ganglion and spinal cord. (17th March 2015) - Kokubun, Souichi; Sato, Tadasu; Ogawa, Chikara; Kudo, Kai; Goto, Koju; Fujii, Yuki; Shimizu, Yoshinaka; Ichikawa, Hiroyuki
Highlights: TRPV1 and TRPV2 channels are multimodal sensors. Sympathetic neurons in human stellate ganglion contained TRPV1 and TRPV2. Sympathetic neurons were surrounded by TRPV2-containing nerve fibers. Lateral horn neurons in human spinal cord have TRPV2. There is TRPV1- or TRPV2-containing sympathetic pathway in stellate ganglion and spinal cord. Abstract: Immunohistochemistry for the transient receptor potential cation channel subfamily V member 1 (TRPV1) and 2 (TRPV2) was performed on the stellate ganglion and spinal cord in human cadavers. In the stellate ganglion, 25.3% and 16.2% of sympathetic neurons contained TRPV1- and TRPV2-immunoreactivity, respectively. The cell size analysis also demonstrated that proportion of TRPV1- or TRPV2-immunoreactive (-IR) neurons among large (>600 μm 2 ) sympathetic neurons (TRPV1, 30.7%; TRPV2, 27.0%) was higher than among small (<600 μm 2 ) sympathetic neurons (TRPV1, 22.0%; TRPV2, 13.6%). The present study also demonstrated that 10.0% of sympathetic neurons in the stellate ganglion had pericellular TRPV2-IR nerve fibers. Fourteen percent of large neurons and 7.8% of small neurons were surrounded by TRPV2-IR nerve fibers. TRPV2-immunoreactivity was also detected in about 40% of neuronal cell bodies with pericellular TRPV2-IR nerve fibers. In the lateral horn of the human thoracic spinal cord, TRPV2-immunoreactivity was expressed by some neurons and many varicose fibers surrounding TRPV2-immunonegative neurons. TRPV2-IR pericellular fibers in the stellate ganglion may originate from the lateral horn of the spinal cord. There appears to be TRPV1- or TRPV2-IR sympathetic pathway in the human stellate ganglion and spinal cord.